Digital Comics as A Media in EFL Reading Classrooms - Atika Diyah Saputri; Sunardi Sunardi; Akhmad Arif Musadad (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to determine student perceptions of Digital Comics as a learning media in senior high school in Surakarta. The design of this study used a survey with a questionnaire given to 80 students of class XI randomly. Data collection techniques using questionnaires. A questionnaire is used to collect data, which is distributed to student population samples. The technique for collecting data is to distribute questionnaires and then analyze the results quantitatively using percentages and analysis tools. The results showed that 79.2% of students were not familiar with digital comics. Learning media can be seen in that 68% use PowerPoint, 24% use books, and 8% use learning videos. Students' perceptions of digital comics' use as a learning media showed that 93% of students agreed, and 7% disagreed with using digital comics in the L2 reading classrooms. This study implies that digital comics' use in the EFL reading classrooms is an alternative activity and provides fun learning for students.